Telicity, change, and state a cross-categorial view of event structure - Demonte, Violeta; McNally, Louise, 1965- (Oxford : Oxford University Press, 2012)
This volume presents work by researchers on central themes in the study of event structure: the nature and representation of telicity, change, and the notion of state. It advances our understanding of these aspects by combining foundational semantic research with a series of case studies from a variety of languages.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Verb phrase; Comparative linguistics